The long tragedy Australian evangelical Christians and the Great War, 1914-1918 - Linder, Robert Dean (Adelaide, SA Open Book, 2000)
Includes bibliographical references and index.
Keywords: Evangelists -- Australia; War -- religious aspects -- Christianity; World War, 1914-1918.